Pengaruh Delivery Strategy yang Berbeda Terhadap Hasil Belajar Pengetahuan Prosedural - Nabilah Riauwati, May Rahmi; Degeng, Made Duananda Kartika; Aulia, Fikri (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study aims to investigate the impact of different delivery strategies on students' learning outcomes, particularly in procedural knowledge in the subject of Bahasa Indonesia for the 11th grade DKV students at SMK Negeri 7 Jember. The research design utilized was a quasi-experiment with a nonequivalent control group pretest-posttest design. The population comprised all 11th-grade DKV classes at SMK Negeri 7 Jember, totaling four classes. Purposive sampling was employed to select XI DKV 1 as the experimental group and XI DKV 2 as the control group. Data were collected through pretests and posttests administered to both groups at the end of the study to obtain students' learning outcomes. Data analysis was conducted using Independent Sample T-Test, revealing a significant influence of different delivery strategies on procedural knowledge learning outcomes in Bahasa Indonesia between the control and experimental groups, as indicated by Sig. (2-tailed) value of 0.000 < 0.05.